In Silico Identification of Heterotrigona itama Propolis Compounds as GC-C Agonists and LGR5 Inhibitors for Colorectal Cancer Chemoprevention - Clara Vinny Amalia; Paula Mariana Kustiawan (Indonesian Journal of Cancer Chemoprevention, 2025)
Abnormal regulation of LGR5 receptors in the Wnt pathway and loss of Guanylyl Cyclase C (GCC) expression have been implicated in the pathogenesis of colorectal cancer, rendering them promising therapeutic targets for further exploration. With the growing focus on natural product-based drug development, Heterotrigona itama propolis emerges as a potential source of bioactive compounds. This in silico study aims to analyze the potential of active compounds from stingless bee propolis as GCC receptor agonists and LGR5 receptor inhibitors and to identify the compounds with the most favorable binding affinity. The results revealed that eleven propolis compounds, including CAPE, Quercetin, Chrysin, 9-octadecenoic acid, Cardol, Cardanol, and Anacardic acid, could bind to both GC-C and LGR5 target receptors. Among these, cardanol had the highest binding affinity for GCC (-7.3 kcal/mol), while Anacardic acid showed the best binding affinity for LGR5 (-6.5 kcal/mol). Overall, the Heterotrigona itama propolis compounds exhibited a stronger binding affinity for LGR5 than for GCC. The substance has good action in binding to the receptor, suggesting that it may be used as treatment to prevent the progression of colorectal cancer. These findings provide a foundational basis for further studies to validate the pharmacological potential of propolis for colorectal cancer treatment.Keywords: cancer, colorectal, LGR5, GCC, propolis.